Rhizobium meliloti host range nodH gene determines production of an alfalfa-specific extracellular signal. - Faucher, C (1988)
The Rhizobium meliloti nodH gene is involved in determining host range specificity. By comparison with the wild-type strain, NodH mutants exhibit a change in host specificity. That is, although NodH mutants lose the ability to elicit root hair curling (Hac-), infection threads (Inf-), and nodule meristem formation (Nod-) on the homologous host alfalfa, they gain the ability to be Hac+ Inf+ Nod+ on a nonhomologous host such as common vetch. Using root hair deformation (Had) bioassays on alfalfa and vetch, we have demonstrated that sterile supernatant solutions of R. meliloti cultures, in which the nod genes had been induced by the plant flavone luteolin, contained symbiotic extracellular signals. The wild-type strain produced at least one Had signal active on alfalfa (HadA). The NodH- mutants did not produce this signal but produced at least one factor active on vetch (HadV). Mutants altered in the common nodABC genes produced neither of the Had factors. This result suggests that the nodABC operon determines the production of a common symbiotic factor which is modified by the NodH product into an alfalfa-specific signal. An absolute correlation was observed between the specificity of the symbiotic behavior of rhizobial cells and the Had specificity of their sterile filtrates. This indicates that the R. meliloti nodH gene determines host range by helping to mediate the production of a specific extracellular signal.